2015
DOI: 10.7759/cureus.414
|View full text |Cite
|
Sign up to set email alerts
|

Durable Disease Control with MEK Inhibition in a Patient with NRAS-mutated Atypical Chronic Myeloid Leukemia

Abstract: Atypical chronic myeloid leukemia (aCML) and chronic neutrophilic leukemia (CNL) are rare hematologic neoplasms characterized by leukocytosis and a hypercellular bone marrow. Although recurrent mutations in the colony-stimulating factor 3 receptor (CSF3R) are frequently observed in patients with (CNL), the mutational landscape in (aCML) is less well-defined. In this report, we describe an 81-year-old male who was diagnosed with aCML. He presented with leukocytosis and anemia but no significant clinical symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…It is acknowledged that not all genetic or epigenetic events resulting in this neutrophilic progression may be resolved by such a targeted approach, however, the utility of exon sequencing in defining clonal evolution and hierarchy underlying transformational events in PMF (Ferrer‐Marín et al , ) can aid in the identification of personalised therapeutic targets. Pharmacological inhibitors of MEK have shown considerable efficacy in BRAF ‐mutated metastatic melanoma, with case reports demonstrating significant clinical responses of these agents, such as trametinib, in NRAS ‐mutated haematological malignancies, including aCML with a similar neutrophilic hyperleucocytosis (Khanna et al , ). In context of the emerging array of treatments for MPN (Vannucchi & Harrison, ) such cases support the rationale for considering clinical trials of MEK inhibitors in the treatment of NRAS ‐mutated MPN.…”
mentioning
confidence: 99%
“…It is acknowledged that not all genetic or epigenetic events resulting in this neutrophilic progression may be resolved by such a targeted approach, however, the utility of exon sequencing in defining clonal evolution and hierarchy underlying transformational events in PMF (Ferrer‐Marín et al , ) can aid in the identification of personalised therapeutic targets. Pharmacological inhibitors of MEK have shown considerable efficacy in BRAF ‐mutated metastatic melanoma, with case reports demonstrating significant clinical responses of these agents, such as trametinib, in NRAS ‐mutated haematological malignancies, including aCML with a similar neutrophilic hyperleucocytosis (Khanna et al , ). In context of the emerging array of treatments for MPN (Vannucchi & Harrison, ) such cases support the rationale for considering clinical trials of MEK inhibitors in the treatment of NRAS ‐mutated MPN.…”
mentioning
confidence: 99%
“…58,59 Treatment with trametinib 2 mg daily produced a durable near-complete hematologic response, with the WBC count decreasing from 256 3 10 9 /L to the 10 3 10 9 to 15 3 10 9 /L range and the platelet count improving from 66 3 10 9 /L to 168 3 10 9 /L. 57 Pharmacologic reactivation of the tumor suppressor PP2A, which is functionally suppressed because of SETPB1 mutations, is a promising therapeutic approach to pursue with drugs such as fingolimod (FTY720). 60,61 Spliceosome modulators are a novel class of therapeutics entering clinical trials for myeloid neoplasms and may have a role in aCML patients with mutations in SRSF2 or other genes that comprise the spliceosome machinery.…”
Section: Future Prospectsmentioning
confidence: 99%
“…A recent example comes from investigators from Oregon Health and Sciences University who identified an NRAS G12D mutation at 47% mutant allele frequency in an aCML patient. 57 The mitogen-activated protein kinase kinase 1 (MEK1)/MEK2 inhibitor tramenitinib, approved for malignant melanoma, also exhibits activity in RAS-driven leukemias in vitro and in vivo. 58,59 Treatment with trametinib 2 mg daily produced a durable near-complete hematologic response, with the WBC count decreasing from 256 3 10 9 /L to the 10 3 10 9 to 15 3 10 9 /L range and the platelet count improving from 66 3 10 9 /L to 168 3 10 9 /L.…”
Section: Future Prospectsmentioning
confidence: 99%
“…The identification of NRAS mutations in a portion of CNL patients has led to speculation that MEK inhibitor therapy with drugs such as trametinib, may provide clinical benefits in certain CNL subsets . As we gain further insight into the genomics of CNL, molecularly‐driven targeted therapy will likely emerge as the definitive treatment approach.…”
Section: Managementmentioning
confidence: 99%